Artificial Intelligence based Desktop Partner - Wasim Alam Rahman, Partha Pratim Gohain, Dibya Jyoti Bora (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Today our lives became additional fast and agitated than ever before. We have a bent to speak, move and learn on-line. The ultimate luxury of having an assistant who always listens for you, takes action when necessary and anticipates your every need is now available through Intelligent Personal Assistants (IPAs) with the help of users communicate through Natural Language Processing (NLP). Within the age of constantly changing and advancing technology, we will do things that we have a bent to never thought that we could have done it before. To achieve the luxury and your thoughts of automatizing and performing tasks of services for an individual this paper aims to develop a Virtual Personal Assistant (VPA) having the power to maneuver just by the human voice. The assistant is designed entirely in python with an agenda of providing control over your desktop. The user’s voice request is captured through the microphone and the result is replied in the form of speech using the built-in speakers. With the promising rising and emerging of the IPAs this voice-controlled virtual assistant helped in transcending our imaginations providing full features of utilizing the desktop technologies on users’ voice directions.